Recent Update of HDAC Inhibitors in Lymphoma - Chen, I-Chung; Sethy, Bidyadhar; Liou, Jing-Ping (Frontiers in Cell and Developmental Biology, 2020)
Modulating epigenetic modification has been recognized for over a decade as an effective therapeutic approach to cancer and many studies of histone deacetylase (HDAC), one of the best known epigenetic modulators, have been published. HDAC modulates cell proliferation and angiogenesis and plays an essential role in cell growth. Research shows that up-regulated HDACs are present in many cancer types and synthetic or natural HDAC inhibitors have been used to silence overregulated HDACs. Inhibiting HDACs may cause arrest of cell proliferation, angiogenesis reduction and cell apoptosis. Recent studies indicate that HDAC inhibitors can provide a therapeutic effect in various cancers, such as B-cell lymphoma, leukemia, multiple myeloma and some virus-associated cancers. Some evidence has demonstrated that HDAC inhibitors can increase the expression of immune-related molecules leading to accumulation of CD8+ T cells and causing unresponsive tumor cells to be recognized by the immune system, reducing tumor immunity. This may be a solution for the blockade of PD-1. Here, we review the emerging development of HDAC inhibitors in various cancer treatments and reduction of tumor immunity.